Puerto Rico Census Project, 1910 - Palloni, Alberto ([Verlag nicht ermittelbar], 2006)
The data comprising the Puerto Rico Census Project, 1910 contain individual and household records drawn from the 1910 Puerto Rican Population Census. The data include variables containing basic demographic information such as age, sex, race, marital status, number of children born and surviving, family size, place of birth, immigration status, county and neighborhood of residence, urban/rural status, and citizenship. The data also describe language proficiency, literacy, school attendance, and disabilities (blind or deaf) of the individuals. Other variables provide data on occupation, industry, ownership of residence, status of mortgage, and farm ownership. There are four classifications of variables belonging to this dataset: original input variables, coded variables, constructed variables, and quality flag variables. The original input variables contain the raw data collected by the enumerators. The coded variables are variables that were recoded by the University of Wisconsin Survey Center (UWSC) as part of the Puerto Rico Census Project. Constructed variables were produced by UWSC to capture additional relevant information. For example, one constructed variable measures literacy by combining separate variables containing data on whether the individual could read and if they could write. Finally, quality flag variables were created by UWSC to indicate whether it could be logically deduced that individual records had been hand edited by the Census Office.